PENGEMBANGAN MEDIA PEMBELAJARAN PENGUKURAN TEKNIK PADA INSTALASI RUMAH TANGGA BERBASIS MACROMEDIA FLASH DI MATA KULIAH PENGUKURAN TEKNIK : PENGEMBANGAN MEDIA PEMBELAJARAN PENGUKURAN TEKNIK PADA INSTALASI RUMAH TANGGA BERBASIS MACROMEDIA FLASH DI MATA KULIAH PENGUKURAN TEKNIK - Ni Luh Rosa Diarsanthi; I Gede Ratnaya; Wayan Mahardika Prasetya Wiratama (Jurnal Pendidikan Teknik Elektro Undiksha, 2022)
This study aims to create a learning media for measuring techniques in household installations based on Macromedia flash that is feasible to use and to find out the responses of students to this media in the Engineering Measurement Course in the D3 Electronic Engineering Study Program. This study uses the Research and Development (R&D) method. Data collection in this study was carried out using a questionnaire or questionnaire method which was assessed by content experts, media experts, and students. The results of the questionnaire to determine the feasibility of Media Measurement Techniques in Household Installations Based on Macromedia Flash. The results obtained: The validation test from content experts gets a percentage of 100%, the validation test results from media experts get a percentage of 91.12%, the results of trials in small groups involving 5 respondents get very decent qualifications with a percentage of 100%, the results large group test of 21 respondents got very good classification. Learning Media of Mechanical Measurement in Household Installations Based on Macromedia Flash in the Engineering Measurement Course at the D3 Electronic Engineering Study Program, Ganesha Education University is suitable for use in the learning process.